Research on PDE-based adaptive anisotropic image registration - Shu-jing JIANG; Bao-qin HEI; Jiu-xing ZHANG; Qian-nan LI (Tongxin xuebao)
A PDE-based adaptive anisotropic model for image registration was proposed to solve the problem that tradi-tional optical flow brings on the image blurring and details losing.The new model introduces adaptivity image registration,and defines anisotropic diffusion function with the ability of preserving image structure as the regu-larization term;the data term use a non-quadratic penalty function with the assumption in brightness constant to improve the robust of the model.The experimental results show that the model can efficiently protect the image structure and achieve accurate registration of the complex image like brain.